2022
DOI: 10.3390/polym14142842
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Oxidized Sucrose and Its Application as a Crease-Resistant Crosslinking Agent

Abstract: Oxidized sucrose is a non-formaldehyde crosslinking agent with many applications in polymer crosslinking and modification, such as in the preparation of starch films and protein films. However, research on the structure of oxidized sucrose is lacking. In this paper, oxidized sucrose was synthesized through selective oxidation of sodium periodate. By LC-MS, FTIR, TGA, NMR, and HRMS analyses, it was shown that oxidized sucrose existed in the form of a hydrate, and the tetraaldehyde oxidized sucrose could isomeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…For this reason, the crosslinking reaction was performed at a low temperature, in this case at 40°C, which means a reduced reaction rate. It was reported that OS has low activation energy for the crosslinking reaction, and the number of aldehyde groups that can participate in the crosslinking process is higher than that found in other crosslinking compounds 29 . This could also support the selection of mild temperatures for SPI‐OS containing PEO.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…For this reason, the crosslinking reaction was performed at a low temperature, in this case at 40°C, which means a reduced reaction rate. It was reported that OS has low activation energy for the crosslinking reaction, and the number of aldehyde groups that can participate in the crosslinking process is higher than that found in other crosslinking compounds 29 . This could also support the selection of mild temperatures for SPI‐OS containing PEO.…”
Section: Resultsmentioning
confidence: 92%
“…It was reported that OS has low activation energy for the crosslinking reaction, and the number of aldehyde groups that can participate in the crosslinking process is higher than that found in other crosslinking compounds. 29 This could also support the selection of mild temperatures for SPI-OS containing PEO. Samples treated during two different times (6 h and 24 h) were compared to the sample without thermal treatment.…”
Section: Electrospun Crosslinked Spi Mats (Spi-os)mentioning
confidence: 89%
“…We performed solubility tests over 2 days using four different solvents: water, 1 M NaOH, 1 M citric acid, and the organic solvent THF. These tests were performed on polymer resins synthesized from oxidized sucrose 49 . The results of this experiment were shown in Figure S3.…”
Section: Resultsmentioning
confidence: 99%
“…These tests were performed on polymer resins synthesized from oxidized sucrose. 49 The results of this experiment were shown in Figure S3. Solubility tests showed that the polymer resin was insoluble in water and 1 M NaOH solution.…”
Section: Characterization Of Recycled Polymer Resinmentioning
confidence: 99%
“…The FTIR spectrum of CTSG 3 after reduction demonstrated the absorption band of secondary amine at 1594 cm −1 [28], suggesting the reduction of the imine bond to secondary amine. The absorption band of the aldehyde group (C=O stretching) was not observed at 1710 cm −1 [23,29] in the spectra of CTSG before and after reduction. The FTIR spectra did not clearly confirm the presence of aldehydes in CTSG and the reduction of aldehydes.…”
Section: Structural Characterizations Of Ctsgsmentioning
confidence: 91%